Analisis Faktor Lingkungan Keluarga dalam Membentuk Kemandirian Belajar Siswa - Suhartono, Suhartono; Marlina, Marlina; Suwandi, Suwandi; Permana, Dika (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2024)
This research aims to analyze family environmental factors in shaping student learning independence. The type used in this research is library research or library study. The research results show that learning independence refers to students' ability to manage their learning process independently, including personal initiative, time management, and problem-solving abilities. Family environmental factors, such as parental parenting, emotional support, and parental education, play an important role in supporting or inhibiting independent learning. Democratic parenting is considered the most effective in developing student independence because it provides freedom with clear boundaries. Positive emotional support, such as positive reinforcement and emotional involvement, also encourages children to learn to be independent. Parental education, especially higher education, has a significant impact in creating a conducive learning environment by providing adequate educational resources and guiding children in solving problems independently. This research emphasizes the important role of the family in forming students' learning independence in order to achieve optimal learning outcomes.